Effect of intestinal pressure on fistula closure during vacuum assisted treatment: A computational approach - Cattoni, Diego I. (2011)
Background: Enterocutaneous fistulae, pathological communications between the intestinal lumen and the abdominal skin, can arise as serious complication of gastrointestinal surgery. A current non-surgical treatment for this pathology involves topical application of sub-atmospheric pressure, also known as vacuum assisted closure (VAC). While this technique appears to be promising, surgeons report a number of cases in which its application fails to achieve fistula closure. Here, we evaluate the fistula's physical properties during the vacuum assisted closure process in a computational approach exploring the relevance of intraluminal intestinal pressure. Methods: A mathematical model formulated by differential equations based on tissue elasticity properties and principles of fluid mechanics was created and forcing functions were integrated to mimic intestinal pressure dynamics. A software to solve equations and to fit the model to experimentally obtained data was developed. This enabled simulations of vacuum assisted fistula closure under different intestinal pressure. Results: The simulation output indicates conditions, in which fistula closure can or cannot be expected suggesting favoured or impeded healing, respectively. When modifications of intestinal pressure, as observed in fistula accompanying pathologies, are integrated, the outcome of fistula closure changes considerably. Rise of intestinal pressure is associated with delay of fistula closure and temporary fistula radius augmentation, while reduction of intestinal pressure during sub-atmospheric pressure treatment contributes to a faster and direct fistula closure. Conclusion: From the model predictions, we conclude that administration of intestinal pressure decreasing compounds (e.g. butylscopolamine, glucagon) may improve VAC treatment, while intestinal pressure increasing drugs should be avoided.